Rehearsals in Bas Relief: Le Marin de Gibraltar of Marguerite Duras - Mechthild Cranston (Studies in 20th & 21st Century Literature, 1993)
With the publication of her first L'Amant in 1984, Marguerite Duras became an instant international best-seller. Seven years later, L'Amant de la chine du Nord received widespread media attention on both sides of the Atlantic. Yet Duras' early work remains virtually unknown to the educated reader here and abroad. Passed off in the Twayne volume on Duras as an imitation of Hemingway, Le Marin de Gibraltar, 1952, has never recovered from that first summary dismissal. The present essay reads Le Marin in light of Kristevan analysis, and attempts to show how the early novel foreshadows Duras' mature oeuvre.
Keywords: L' Amant; Marguerite Duras; L' Amant de la chine du Nord; early works; Le Marin de Gibraltar; review; Kristevan analysis